An Integrated Farming Model for Community Empowerment and Environmental Conservation in Kawasi Village - Lukmanul Hakim; Latif Supriadi; Lusty Rahmatina; Dian Nurcahya (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
This community service program aims to describe and analyze the implementation of the SALAM KAWASI Program (Kawasi Integrated Farming System) by PT Trimegah Bangun Persada Tbk (PT TBP) as a form of sustainable Corporate Social Responsibility (CSR). Located in Kawasi Village, Obi Island, the program was designed as an integrated farming model combining horticulture (PERTIKAT), freshwater aquaculture (BUDIKASI), and livestock. The implementation method utilized a participatory approach involving intensive mentoring, learning-by-doing training, and the establishment of a core community group. The results demonstrate that the program successfully enhanced the capacity and income of group members, with an average income increase of IDR 1,200,000 per month per member. A social innovation named KOPASKAT (Compost for Community Agriculture) emerged as a solution for converting organic waste into fertilizer, supporting the transition towards sustainable agriculture with a trend of reducing chemical fertilizer use from 70% (2023) to 50% (2025). The program's success was bolstered by effective multi-stakeholder collaboration and a process of local leadership regeneration. In conclusion, PT TBP's SALAM KAWASI Program has proven to be an effective empowerment model that emphasizes alignment with local needs, active participation, and ecological sustainability, serving as a potential benchmark for similar initiatives.